Cognitive reserve modulates attention processes in healthy elderly and amnestic mild cognitive impairment: An event-related potential study. Issue 1 (January 2018) - Gu, Lihua; Chen, Jiu; Gao, Lijuan; Shu, Hao; Wang, Zan; Liu, Duan; Yan, Yanna; Li, Shijiang; Zhang, Zhijun
Highlights: Higher cognitive reserve (CR) results in better task performance via lowering neural inefficiency in elderly healthy controls (HC). CR differently modulates attention processes in HC and amnestic mild cognitive impairment (aMCI) patients. CR lowers cognitive impairment of HC and aMCI patients. Abstract: Objectives: The study aimed to investigate and compare the effect of cognitive reserve (CR) on brain activation in healthy controls (HC) and amnestic mild cognitive impairment (aMCI) patients during 0-back and 1-back tasks measured by event-related potential (ERP). Methods: The study recorded 85 subjects (39 aMCI patients and 46 their matched controls) with a 64-channel electroencephalogram (EEG). Subjects performed 0- and 1-back tasks. Results: Compared to HC, aMCI patients showed reduced accuracy, delayed mean correct response time (RT) and decreased P300 amplitude at central-parietal and parietal electrodes. A mediation analysis indicated that higher CR reduced neural inefficiency, which might be associated with better task performance in HC. However, no correlation was detected between CR and neural inefficiency in aMCI patients, whereas higher CR was still related to enhanced accuracy and prolonged RT in aMCI patients. Conclusions: The present study reported that higher CR could contribute to better task performance via down-regulating neural inefficiency in HC. In addition, higher CR might modulate attention processes in aMCI via a way distinct from that in HC, and eventually result in better task performance. Significance: The study provided evidence for that improving CR might lower cognitive impairment of healthy elderly and aMCI patients.